Research on the selection of polyurethane adhesive and direct tensile properties of polyurethane rubber particle mixture - Junfeng Gao; Jiakang Chen; Xianwei Meng; Hainian Wang; Ning Xu (Case Studies in Construction Materials, 2023)
Poroelastic road surface has been found to be an effective solution for the traffic noise due to their porosity and elastic properties compared with conventional asphalt surface. However, the appropriate polyurethane for road utilization is still unclear and undetermined, the tensile properties of polyurethane rubber particle mixture based on different types of polyurethane adhesive and rubber particles were rarely studied. This study aims to primarily select the road polyurethane adhesive, investigate the stage changes during the tensile test and the interface change after the fracture of polyurethane rubber particle mixture (PRPM). Rubber particles with one size and four different types (F2, F5, T, TA) of polyurethane with five dosages (15 %, 18 %, 21 %, 24 %, 27 %) were adopted to prepare polyurethane rubber particle mixtures. A bonding and curving equipment based on direct tensile test was developed, while a dog bone shape mold for forming specimens was self-designed. The results showed that the direct tensile change process of polyurethane rubber particle mixture could be divided into four stages: reaction delay stage, elastic deformation stage, fracture stage and post-fracture stage. With the increase of polyurethane content, the damaging effect of the mixture gradually transitioned from the polyurethane-rubber interface adhesion to the polyurethane-polyurethane interface binder cohesion. The polyurethane rubber particle mixture with polyurethane type F2 had high tensile properties at a content of 18 %.